Iron(II) chloride enhances the biocontrol activity of Pseudomonas fluorescens against root-knot nematodes (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Pradana AP, Hoesain M, Asyiah IN, Adiwena M, Angelina Y, Putri D, Masnilah R, Dewi RR. 2025. Iron(II) chloride enhances the biocontrol activity of Pseudomonas fluorescens against root-knot nematodes. Biodiversitas 26: 4243-4256. Root-knot nematodes (Meloidogyne incognita) account for over 15% of global crop losses, highlighting the urgent need for sustainable biocontrol solutions. Microbial-based strategies, particularly those employing Pseudomonas fluorescens, present environmentally responsible alternatives to chemical nematicides while enhancing soil microbial diversity. The aim of this study was to evuluate the systematic assessment of Iron(II) Chloride (FeCl?) supplementation for improving the nematicidal efficacy of P. fluorescens. Five treatment combinations of FeCl? (0, 50, and 75 ppm) and pH (6 and 8) were evaluated in vitro. The results showed that at 24 hours, J2 mortality reached 16.8% in the 75 ppm FeCl? treatments (pH 6 and 8), significantly exceeding the control (4.4%, p
Keywords: FeCl2, Meloidogyne incognita, methyl linoleate, Pseudomonas fluorescens, secondary metabolites